Deep Learning with TensorFlow : Explore neural networks and build intelligent systems with Python, 2nd Edition. - Zaccone, Giancarlo (Packt Publishing, 2018)
Compliant with TensorFlow 1.7, this book introduces the core concepts of deep learning. Get implementation and research details on cutting-edge architectures and apply advanced concepts to your own projects. Develop your knowledge of deep neural networks through hands-on model building and examples of real-world data collection.